Analisis Pembiayaan Ijarah Pada Perbankan Syariah - Harun Santoso; Anik Anik (ITB AAS INDONESIA Surakarta, 2015)
This study is to analyze Ijarah financing in Islamic banking. Theories related to this study include about Ijarah, Ijarah financing, DSN-MUI fatwa, Ijarah financing application. This study is a qualitative descriptive study which is conducted in 2016. Data collection methods used is study literature.The result of this study shows that the product is based on the principles of Islamic banking financing leases consist of pure rents and leases, which ended with the transfer of ownership, known as Ijarah muntahiya bit Tamlik. Ijarah Muntahia bit Tamlik or IMBT is basically a mix between a lease with purchase.Keywords: Ijarah and Ijarah Mutahiya Bit Tamlik (IMBT)